Algorithm of construction of the type and its realization in the language W - Todorova, Magdalina; Birov, Dimitar (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
The notion of polymorphism describes data, which possess more than one type, or functions, which operate over a set of types in programming languages. In this paper an implementation of Milner's polymorphic type interface algorithm is described. It is proved that the algorithm is sound, effective and supports a rich and flexible type system. A programming language with equations and unification W is used.